Towards the development of a manufacturing failure mode avoidance framework for aerospace manufacturing - Goodland, J; Campean, I; Victory, J; Caunce, A (Cranfield University Press, 2013)
A process based management strategy is crucial to enable productivity and cost effectiveness enhancement in high value manufacturing. This paper introduces a Manufacturing Failure Mode Avoidance (MFMA) framework based on four high level steps, underpinned by a series of structured tools to support a structured function-based decomposition of complex manufacturing processes and a continuous flow of information towards the development of robust control plans. The approach draws from experience from the automotive industry where Failure Mode Avoidance (FMA) has been adopted as a strategy to achieve a step change in the effectiveness of business and engineering processes associated with the product creation process. The paper illustrates a pilot implementation of the MFMA framework on a case study for the manufacturing of an aerospace component, followed by a discussion of the broader applicability of the framework and directions for further work.
Keywords: Failure Mode Avoidance; Process FMEA; Robust Process Control Planning